ANALISIS KONVERSI HUTAN MANGROVE DI KECAMATAN GEBANG KABUPATEN LANGKAT (Conversion Analysis of Mangrove in District Gebang, Langkat) - Rika Wirani; Yunasfi Djayus; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Mangrove is continuously under pressure due to various human activities. Lack of understanding about the importance of mangrove ecosystems and the increasing of life needs has sparked a mangrove conversion occurs. This research analyzed the conversion of mangrove in the district gebang, langkat from 2003 to 2012 using image of landsat ETM 7+ satellite of 2003 year and 2012 year and its impact to the economic situation of the fisherman. The landuse in district Gebang are ground, mangrove, rice field, pond, plantations, dryland, farming bush, residence, and water. The landuse of mangrove in the district Gebang decreased by 79,96% from 2003 to 2012. Extensive mangrove which have been converted into ponds is 276,96 ha, 1.520,46 ha of plantations, and 313,10 ha of farming bush. The catches of fisherman has decreased into 30,71% and fishing income decreased into 51,37%.Keywords : Land conversion, mangrove, landsat ETM 7+